Covalent Organic Frameworks - Gao, Yanan; Lu, Fei (IntechOpen, 2023)
In recent decades, artificial porous structures have attracted increasing enthusiasm from researchers inspired by the fascinating molecular pores in nature and their unique biological functions. Although substantial achievements in porous materials have been realized, the construction of topologically designed pores is still challenging. Recently, the emergence of covalent organic frameworks (COFs), which are constructed based on organic and polymer chemistry, has made it possible to design artificial pores with controlled pore size, topology and interface properties. COFs are crystalline porous materials constructed by the precise reticulation of organic building blocks via dynamic covalent bonds. Distinct from non-covalent interactions which tend to produce isostructures, covalent bonds enable accurate pore design owing to their predetermined reaction pathways. In addition, the appropriate polycondensation of organic building units enables the formation of extended two-dimensional (2D) and three-dimensional (3D) polymer architectures with periodically ordered skeletons and well-defined pores. With their large surface area, tailorable structures, and tunable chemistry, COFs are regarded as potentially superior candidates for various applications including catalysis, energy storage and conversion, mass transport and biotechnology. This book examines the historic achievement of COFs, providing clear and comprehensive guidance for researchers on their structural design, synthetic protocols and functional exploration.